EFFECT OF ENVIRONMENTAL PARAMETERS ON THE VALUE OF HUE SAND DOLLARS IN KARIMUNJAWA ISLANDS CENTRAL JAVA INDONESIA - Suryanti Suryanti; Sutrisno Anggoro; Churun A’in; Wiwiet Teguh Taufani (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2022)
Sand dollar is one among many echinoid groups with unique habitat preferences in the coastal waters. The hue (color) of sand dollar is one of the unique aspects, but currently, the information is still very limited. The purpose of this study is to investigate the value of hue sand dollar in Karimunjawa waters and investigate the condition of environmental parameters in Karimunjawa waters so that it can further analyze the environmental effect on hue sand dollar levels descriptively. The research was carried out in Karimunjawa islands, including Karimunjawa, Menjangan Kecil, and Cemara Kecil islands in June – July 2019. Sampling was carried out using line-transect with the transect length of 25 m. Four sampling stations were occupied at each island. The observation parameters were including sea surface temperature, pH, DO, organic matter, and seafloor coverage such as coral, rubble, and sand. Hue value was analyzed with Haphazard sampling method, using Adobe Photoshop. Data analysis was conducted with ANOVA and regression. The result showed there were variations in environmental parameters, including the significant difference of pH, organic matter, and rubble coverage. The hue of sand dollar has also differed significantly among islands.  Regression analysis showed significant effect from pH, coral coverage and rubble coverage on the hue value of sand dollar with the formula: ln (Y) = 20.867– 2.364(X1) + 6.608e-5(X2)+ 1.271e-4(X3); while the determination coefficient was 0.849 (p = 0.001). The effect of environmental parameters on the hue value of sand dollar might occur indirectly, but due to the change of pigment composition and concentration.